Pergelaran Seni Pertunjukan Melalui Media Digital Dalam Pembelajaran Seni Budaya Di Sman 5 Bukittinggi - Handayani, Lucy (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
Performing Arts Performances through Digital Media in Cultural Arts Learning at SMAN 5 Bukittinggi is an activity carried out to take the end of odd semester scores with Performing Arts material. This study aims to describe the forms of performing arts performances for class XII and reveal the importance of learning performing arts digitally in class XII at SMA Negeri 5 Bukittinggi.The method used in this study is a qualitative research method with a phenomenological approach. Data collection techniques used are library research, observation, interviews, and documentation.The results of this study found that the implementation was live and watched by students, teachers, and the public through the Zoom, YouTube, Instagram applications. The material that is being performed is music, dance, theater or drama. This performance is important for students to do as an alternative to implementing art performances during a pandemic and can improve better learning outcomes. This art performance can also be carried out flexibly, efficiently, saving time and costs and reaching a wider audience.